PERLINDUNGAN HUKUM PELAUT DI KAPAL INDONESIA BERBASIS NILAI KEADILAN - Tri Cahyadi (UNISSULA, 2017)
This paper discusses the legal protection for sailors on Indonesian Ships amid the many problems experienced by Indonesian sailors. The belence between what has been done with the wages received by Indonesian sailors should be felt by Indonesian sailors has not been releazed, where in case of industrial relation disputes so far can not be resolved fairly, especially about the work place that is on the ship with the location always nomaden. Primary data sources were obtained from interviewers with several Indonesia sailors, as well as the secondary data sources of reference related legislation. The results show that many Indonesian sailors who are unaware of the legal certainty/lack of awarness and understanding of sailors about the relevant law or regulation are factors inhibiting implementation in the field. In addition, low discipline inthe management of income to ensure life on the old days.